Conductometric biosensor based on whole-cell microalgae for assessment of heavy metals in wastewater - Berezhetskyy, A.L.; Durrieu, C.; Nguyen-Ngoc, H.; Chovelon, J.-M.; Dzyadevych, S.V.; Tran-Minh, C. (Біополімери і клітина, 2007)
Whole-cell Chlorella vulgaris conductometric biosensors consisting of gold planar interdigitated electrodes and sol-gel algal membranes have been used for assessment of heavy-metal ions in water. These analytes act as algal alkaline phosphatase inhibitors. Enzyme residual activity has been measured in Tris-nitrate buffer in the presence of Mg²⁺ ions as activator. Operating conditions of this biosensor have been optimized and its characteristics are discussed. Detection limits are about 1 ppb for Cd²⁺, Co²⁺, Ni²⁺, Pb²⁺ and 10 ppb for Zn²⁺. The storage stability of the biosensor in buffer solution at 4 oC is more than 40 days. The biosensor has been used to assess wastewater pollution.